PS1-29: Changing the Culture of Medicine: An Exploration of Lean Healthcare in Primary Care - Gray, Caroline (Clin Med Res, 2014)
BACKGROUND/AIMS: Despite its soaring costs, healthcare in the U.S. still suffers from inefficiencies and wastefulness. Given recent health care reform efforts, healthcare organizations know significant change is on the horizon, and in anticipation of that, some organizations have begun adopting delivery systems that address these wastes and inefficiencies. One system that has gained considerable attention in recent years is commonly referred to as Lean Healthcare. Originating from the manufacturing industry, this approach to healthcare focuses on retaining value for the patient and eliminating non-value or waste. However, implementing Lean healthcare is not without its challenges. One major challenge to implementing Lean is essentially cultural. More specifically, the values and norms associated with Lean and those deeply entrenched in the field of medicine may conflict, and therefore reconciling them may be necessary to successfully implement Lean. METHODS: This study consists of a qualitative evaluation of a Lean implementation effort at a large healthcare organization. Researchers conducted observations of key implementation events and interviewed frontline leaders, as well as physicians, nurses, and medical assistants who have participated in the change effort. The data produced from these qualitative methods were analyzed and coded using an inducted, grounded approach. RESULTS: This paper highlights five main major changes that produced cultural conflict when this healthcare organization implemented Lean. These include: (1) adopting team care approaches (2) democratization of the workplace and the erosion of hierarchies (3) reducing variation and standardizing work (4) surveillance of staff and employees (5) a perceived emphasis on profit over patient care. CONCLUSIONS: Implementing new ways of delivering care in healthcare organizations is often met with many challenges. Some of these challenges may be rooted in a conflict between new sets of cultural values and those that have historically existed in the field of medicine. Reconciling these conflicts may be one of the most difficult challenges healthcare organizations face as they try to implement wide- scale change.